The Doha Development Round: Missed Opportunity or Lucky Escape? - Wade, Robert (Eurostudia)

(untitled) (Le Centre canadien d'études allemandes et européennes, 2007)
AbstractGiven the deadlock of the Doha Round, most of the commentators pointed to the risks of this failure. Contrary to this standpoint, the article sees the abandon of negotiations rather as a chance for escape from a system that did not deliver the outcomes needed. What the future shall bring is first a better equilibrium between trade and financial markets and second a just treatment of developing countries’ interests. The article ends with some propositions in that sense.